2015
DOI: 10.3892/ijo.2015.2908
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone radiation causes brain tumors and should be classified as a probable human carcinogen (2A) (Review)

Abstract: Abstract. Quickly changing technologies and intensive uses of radiofrequency electromagnetic field (RF-EMF)-emitting phones pose a challenge to public health. Mobile phone users and uses and exposures to other wireless transmitting devices (WTDs) have increased in the past few years. We consider that cerenat, a french national study, provides an important addition to the literature evaluating the use of mobile phones and risk of brain tumors. The CERENAT finding of increased risk of glioma is consistent with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 25 publications
(30 reference statements)
0
58
0
5
Order By: Relevance
“…Morgan et al also stated that until further evidence is available, it is prudent to follow the ALARA standard used in pediatric radiology. The ALARA approach would require hardware and software designers to create proximity sensors and embed flash notices regarding simple advisories about safer use within devices [12].…”
Section: Precautionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morgan et al also stated that until further evidence is available, it is prudent to follow the ALARA standard used in pediatric radiology. The ALARA approach would require hardware and software designers to create proximity sensors and embed flash notices regarding simple advisories about safer use within devices [12].…”
Section: Precautionsmentioning
confidence: 99%
“…Childhood brain tumors have been linked to it in several reports and it might have some significance. But again a large database and definite evidence is still to come out [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, there has been a different interpretation of statistics [8]. Other factors, such as an improved access to care, may have played a role [33].…”
Section: Mobile Phones: Carcinogenic and Other Potential Risksmentioning
confidence: 99%
“…This has been demonstrated neither for glioma nor for meningioma [18]. However, in other studies, the risk of glioma increased with increasing time since the first mobile phone use or with increasing cumulative call time [8,10,11]. Considering potential biases in epidemiological research, cumulative effects should be verified in experiments.…”
mentioning
confidence: 95%
“…2,5,6 Though conflicting evidence exists, it has been suggested that these radiofrequency fields should be classified as a 'probable' human carcinogen. 7 No interaction between mobile phone usage and auditory function was demonstrated when testing several audiological parameters. [8][9][10][11] However, a few recent studies did find that mobile phone users had a significantly greater risk of having elevated thresholds in the speech frequencies 9 or high frequencies (above 8 kHz), 10,11 and absent distortion product otoacoustic emissions.…”
Section: Introductionmentioning
confidence: 99%